2019
DOI: 10.1136/bmjopen-2019-029084
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and quality of life (QoL) of head and neck cancer and brain tumour survivors in Pakistan: an analytical cross-sectional study protocol

Abstract: BackgroundCancer is a devastating disease and has detrimental effects on the quality of life (QoL) of cancer survivors and interferes with their treatment compliance. The aim of the study is to assess resilience and QoL among cancer survivors and to evaluate the important factors affecting their resilience and QoL, with respect to the Pakistani cultural context.Method and analysisA cross-sectional study will be conducted at a tertiary care hospital in Karachi, Pakistan. A minimum sample size of 250 head and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(50 citation statements)
references
References 46 publications
(45 reference statements)
1
49
0
Order By: Relevance
“…Resilience, defined as the capacity of individuals to maintain stable physical and mental functionality in the face of adversity, has been shown to help protect against psychological distress in cancer patients 8 ,. 9 Available literature supports the hypothesis that resilience is a product of multifactorial influences that include illness‐related factors (uncertainty of the illness, disease‐related distress, and treatment‐related distress), individual‐related factors (level of education, personality traits, and coping mechanisms), family related factors (family resources and income, family support, and family structure), and social factors (interpersonal relationships, social integration, and professional/work involvement) 9‐11 . In addition, resilience is closely related with mental health, particularly depression and anxiety 9 ,.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Resilience, defined as the capacity of individuals to maintain stable physical and mental functionality in the face of adversity, has been shown to help protect against psychological distress in cancer patients 8 ,. 9 Available literature supports the hypothesis that resilience is a product of multifactorial influences that include illness‐related factors (uncertainty of the illness, disease‐related distress, and treatment‐related distress), individual‐related factors (level of education, personality traits, and coping mechanisms), family related factors (family resources and income, family support, and family structure), and social factors (interpersonal relationships, social integration, and professional/work involvement) 9‐11 . In addition, resilience is closely related with mental health, particularly depression and anxiety 9 ,.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Available literature supports the hypothesis that resilience is a product of multifactorial influences that include illness‐related factors (uncertainty of the illness, disease‐related distress, and treatment‐related distress), individual‐related factors (level of education, personality traits, and coping mechanisms), family related factors (family resources and income, family support, and family structure), and social factors (interpersonal relationships, social integration, and professional/work involvement) 9‐11 . In addition, resilience is closely related with mental health, particularly depression and anxiety 9 ,. 12 Comorbidities, which are frequently present in brain tumor patients, 13 may also affect resilience and mental health 14 ,.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resilience is associated with lower levels of suffering, better ability to adjust, and better QOL among caregivers of patients with stroke, and it could help individuals respond to care‐related psychological challenges 18 . Several researchers have reported that resilience affects many aspects assessed by the WHOQOL, and more resilient caregivers of patients with stroke have significantly better WHOQOL scores 19, 20 …”
Section: Introductionmentioning
confidence: 99%
“…(17) According to recent data, the prevalence of head and neck cancer is escalating in Pakistan, and limited information is available regarding resilience of head and neck cancer in our setting, a low middle-income country (LMIC) having diverse cultural, social and economic factors. (18) This study will bridge this gap and its findings would be beneficial in formulating targeted interventions as per need to improve resilience. This study aims to assess resilience and its associated factors in head and neck cancer patients, posttreatment (≥ 4 wks).…”
mentioning
confidence: 98%